Mga kakagamitang panturo sa Pilipino sa pinatnubayang pagsulat para sa mga estudyanteng Waray sa ikaapat na grado - Canete, Charita C. 1829 ([Quezon City s.n.], 1974)
This study presented instructional materials in guided composition writing. Salient features of this paper include: specific writing skills that should be developed in Waray Grade four learners; different methods, approaches and techniques in guiding the writing ability of the pupils; and various exercises arranged according to the degree of difficulty and designed to develop the writing ability.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Pilipino language -- Study and teaching (Elementary)